2020
DOI: 10.3390/app10082691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hydraulic, Physical, and Mechanical Properties of Pervious Concrete Using Iron Tailings as Coarse Aggregates

Abstract: Aggregates are a significant component of pervious concrete. Pervious concrete using iron tailings as coarse aggregates was prepared to study the feasibility of this approach. A mix design procedure was also used to design pervious concrete based on different target porosities. The effective porosity, measured porosity, dry density, compressive strength, and permeability coefficient of pervious concrete were studied. The results show that the mix design procedure based on a target porosity is relatively reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The iron ore tailings are generated by the waste rock mechanism stripped from the open-pit mine. Compared with ordinary natural aggregate, the IOT has a larger bulk density due to the iron content inside, leading to the natural sinking and difficulty of mortar binding with the aggregate [16]. When IOT is used as a fine aggregate, the specific surface area is large, and the water absorption is high due to the internal stone powder, which worsens the workability of the IOT concrete.…”
Section: Workabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The iron ore tailings are generated by the waste rock mechanism stripped from the open-pit mine. Compared with ordinary natural aggregate, the IOT has a larger bulk density due to the iron content inside, leading to the natural sinking and difficulty of mortar binding with the aggregate [16]. When IOT is used as a fine aggregate, the specific surface area is large, and the water absorption is high due to the internal stone powder, which worsens the workability of the IOT concrete.…”
Section: Workabilitymentioning
confidence: 99%
“…Compared with the natural aggregate, the IOT aggregate in concrete is made from the waste stone stripped from the open-pit mine through crushing and screening [16]. The IOT coarse aggregate has many edges and corners [17].…”
Section: Introductionmentioning
confidence: 99%
“…Iron tailings are inert at room temperature [ 26 , 27 ]. Previous studies have used iron tailings as coarse [ 28 , 29 ] and fine aggregates [ 30 , 31 , 32 , 33 , 34 , 35 ], as well as silica materials for the production of aerated concrete at high temperatures [ 36 , 37 , 38 ]. Some studies have also used iron tailings as an admixture [ 39 , 40 , 41 , 42 , 43 , 44 ] and examined the activation of iron tailings powder [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chloride diffusion is strongly dependent on the microstructural features. Tan et al [ 6 ] reported that pore volume accounts for 5.2–27.2% of concrete. Pivonka et al used scale-transition analysis and predicted that chloride diffusivity in the pore solution is much smaller compared to bulk salt solutions due to the structuring of water molecules along the charged micropore surface [ 7 ].…”
Section: Introductionmentioning
confidence: 99%